Musical sense-making between experience and conceptualisation: the legacy of Peirce, Dewey and James - Reybrouck, Mark (Interdisciplinary Studies in Musicology, 2018)
This contribution revolves around the concept of musical sense-making. Starting from the seminal works of Peirce, Dewey and James, it focusses on the musical experience, which can be defined from an empiricist position as a process that calls forth epistemic interactions with the sounds. Central in this approach is the tension between the richness and fullness of the musical experience and the cognitive economy of symbolic abstraction. Dewey, in particular, has stressed the role of having an experience proper as a kind of heightened vitality. James, on the contrary, has dealt with the distinction between percept and concept, stressing the role of knowledge-by-acquaintance as the kind of knowledge we have of something by its presentation to the senses. In what he coined as radical empiricism he states that the significance of concepts always consists in their relation to perceptual particulars, which, in turn, are embedded in a conceptual map. This map can be described in semiotic terms, which holds a symbolic approach to cognition to the extent that it is concerned with signs rather than with sensory realia. The question should be raised, however, as to the nature of these signs. There is, in fact, a critical distinction between internal and external semantics with signs referring primarily to themselves or to something external to the music. In an attempt to bring these claims together, it is argued that musical signs should provide a self-referential semantics for which the abstract is really material, a real semiotics of singular potential wich is grounded in the real and natural experience. Reying on some grounding work of Peirce and Morris and the relation between signs and tool using, a theoretical framework is introduced that has at least some operational power in going beyond a merely acoustic description of the music as it sounds.